Prevalence and Risk Factors of Postpartum Urinary Retention Following Vaginal Delivery - Nadia Al-Dujaili; Mohanad Albayyaa; Mazin Al-Dujaili; Shahla Alaf (Journal of Scientific Innovation in Medicine)
Background: Postpartum urinary retention (PPUR) is the lack of spontaneous micturition for over six hours post-delivery. Its incidence varies due to differing definitions and risk factors. Objective: To determine the prevalence of PPUR following vaginal delivery at the Maternity Teaching Hospital in Erbil and identify associated risk factors. Methods: This descriptive cross-sectional study was conducted over a year from April 1, 2019, to March 31, 2020. A sample of 500 women who delivered vaginally was analyzed. PPUR was defined as failure to void spontaneously within six hours post-delivery or a post-void bladder volume >150 cc. Results: PPUR was observed in 49 (9.8%) women. Significant risk factors included obesity, nulliparity, late gestational age, induction of labor, episiotomy, and perineal tear. Multiple logistic regression identified later gestational age, longer second stage of labor, induction of labor, and episiotomy as significant predictors of PPUR (p = 0.03, OR = 0.6; p < 0.001, OR = 0.8; p = 0.02, OR = 4.6; p = 0.001, OR = 0.01, respectively). Conclusions: The prevalence of postpartum urinary retention (PPUR) observed in this study is consistent with findings from previous studies. Early detection and proactive management of risk factors are essential for mitigating complications related to PPUR and urinary tract infections. Implementing routine screening and timely interventions can significantly improve postpartum care and patient outcomes.